Corpus of Middle Babylonian and Middle Assyrian incantations - Zomer, Elyze (Leipziger altorientalistische Studien., 2018)
The present volume is the first systematic treatment of the Corpus of Middle Babylonian and Middle Assyrian Incantations. It comprises an exhaustive and detailed catalogue of all magical material in cuneiform texts in Sumerian and Akkadian from the Middle Babylonian and Middle Assyrian periods (ca. 1500-1000 BCE). The work begins with a typology of the different sub-groups of incantations, the physical properties of the tablets, an innovative survey of the text formats, a discussion of drawings on magical texts and a critical discussion of the different paratextual comments, followed by an overview of the geographical and archival setting and an examination on the social context of the corpus. The circulation of magical texts during the Late Bronze Age is investigated by outlining the corpus itself: its thematic grouping of incantations, division of unilingual and bilingual texts, local scribal traditions and their influences. With respect to the question of whether the standardization of incantations took place in Mesopotamia during the Second Millennium, an extensive chapter provides a comparative analysis of the incantation corpora of the Third and Second Millennium against the standardized ritual series of the First Millennium. Fifty cuneiform texts have been edited and translated, accompanied by a thorough philological commentary.